Integrating metagenomics and culturomics to uncover the soil bacterial community in Asparagus cochinchinensis cultivation - Yu, Jingsheng; Yang, Shuai; Zhang, Xiaoyong; Liu, Xiongwei; Tang, Xuebo; Wang, Liuyan; Chen, Jinglan; Luo, Huimin; Liu, Changmin; Song, Chi (Frontiers in Microbiology, 2024)
Asparagus cochinchinensis is a medicinal plant in China, which has gained attention owing its protective effect in human health. However, there are seldom studies to systematically reveal the rhizosphere bacterial community of A. cochinchinensis. In this study, we employed metagenomics and culturomics to analyze the bacterial community composition and diversity in continuous rhizosphere soil of A. cochinchinensis. Meanwhile, we assessed the effect of soil physicochemical properties on the bacterial community. Results showed that the most abundant TAXA is a taxon belonging to the family Streptomycetaceae, the genus Mycobacterium and the species Oligotropha carboxidovorans. The bacterial communities across various areas were similar. Significant differences of exchangeable magnesium and available phosphorus level were observed between three groups. Furthermore, bacterial community structure correlated closely with soil physicochemical properties. Additionally, a total of 103 strains were isolated and identified, representing 28 species. Based on this study, the rhizosphere bacterial community of A. cochinchinensis might influence its growth and development. The rhizosphere strains were isolated and their function request further investigation. This study firstly revealed the bacterial community in the A. cochinchinensis rhizosphere soil, providing valuable references for its quality improvement in practical cultivation process.